The European Sectoral Social Dialogue: Actors, Developments and Challenges - Mangan, David (Relations industrielles / Industrial Relations, 2010)
The European Sectoral Social Dialogue: Actors, Developments and Challenges, edited by Anne Dufresne, Christophe Degryse and Philippe Pochet, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor law; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social change